Iklan Sebagai Media Kritik Sosial (Pesan Simbolik Iklan Kretek Djarum 76 Seri Jin) - Ersyad, Firdaus Azwar; Putro, Yoga Rarasto (Universitas Semarang, 2016)
The presence of television advertising is a prayer one way to manufacturer for review introduce and selling products for society. Regarding the regulation of advertising especially cigarettes and tobacco products manufacturer in order to encourage creative hearts introducing more on audience their product . As a result , the creativity in the hearts smoking ads aimed lifting product image so not operate direct products display .Singer study originated from the interest against visualization advertisements Djarum 76 series java jin has its own peculiarities compared to other products . Zoom the one consolation is not revealed that an advertiser is selling products . Views are interpreted by different groups various ad viewers, but the views can be grouped into some basic ideas